2009
DOI: 10.1104/pp.109.140053
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide Reductase Regulation in Response to Genotoxic Stress in Arabidopsis

Abstract: Ribonucleotide reductase (RNR) is an essential enzyme that provides dNTPs for DNA replication and repair. Arabidopsis (Arabidopsis thaliana) encodes three AtRNR2-like catalytic subunit genes (AtTSO2, AtRNR2A, and AtRNR2B). However, it is currently unclear what role, if any, each gene contributes to the DNA damage response, and in particular how each gene is transcriptionally regulated in response to replication blocks and DNA damage. To address this, we investigated transcriptional changes of 17-d-old Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 36 publications
3
57
0
Order By: Relevance
“…In Arabidopsis, bleomycin triggers a DSB stress response (Menke et al, 2001;Tamura et al, 2002;Chen et al, 2008), whereas hydroxyurea induces a replication stress response (Ferreira et al, 1994;Roa et al, 2009). Treating wild-type and Whirly mutant plants with bleomycin (see Supplemental Figure 7 online) or hydroxyurea (see Supplemental Figure 8 online) did not result in an increase in plastid or mitochondrial MHMR.…”
Section: The Dna Rearrangements Are Induced Mainly By Stresses Targetmentioning
confidence: 98%
See 1 more Smart Citation
“…In Arabidopsis, bleomycin triggers a DSB stress response (Menke et al, 2001;Tamura et al, 2002;Chen et al, 2008), whereas hydroxyurea induces a replication stress response (Ferreira et al, 1994;Roa et al, 2009). Treating wild-type and Whirly mutant plants with bleomycin (see Supplemental Figure 7 online) or hydroxyurea (see Supplemental Figure 8 online) did not result in an increase in plastid or mitochondrial MHMR.…”
Section: The Dna Rearrangements Are Induced Mainly By Stresses Targetmentioning
confidence: 98%
“…Bleomycin and hydroxyurea treatments were performed as described (Chen et al, 2008;Roa et al, 2009). The why2-1 and why1 why3 mutant lines (formerly called KO2 and KO1/3, respectively) were described previously (Maré chal et al, 2008(Maré chal et al, , 2009).…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Since DNA damage highly accumulated in the ae7 mutant, we next examined expression of several genes that are often induced in the DNA damage response. The tested genes included PARP genes that encode poly (ADP-ribose) polymerases required for the maintenance of DNA integrity during replication (DoucetChabeaud et al, 2001), BREAST CANCER SUSCEPTIBILITY1 (BRCA1) and GAMMA RESPONSE1 (GR1) that are involved in DSB repair by the homologous recombination (HR) pathway (Lafarge and Montané, 2003;Bleuyard et al, 2005), KU70, KU80, and LIGASE4 (LIG4) that are required for DSB repair by the nonhomologous end joining pathway (Tamura et al, 2002;van Attikum et al, 2003), TSO2 that is activated in response to DSBs, and RIBONUCLEOTIDE REDUCTASE 2A (RNR2A) and RNR2B that are specifically induced by hydroxyurea (Wang and Liu, 2006;Roa et al, 2009). Our real-time quantitative RT-PCR (qRT-PCR) showed that among the genes tested, transcript levels of PARP1, PARP2, BRCA1, GR1, and TSO2 were elevated in ae7 (Figure 2A).…”
Section: The Ae7 Mutation Causes Dna Damagementioning
confidence: 99%
“…HU induces replication stress by inhibiting the RIBONUCLEOTIDE REDUCTASE (RNR) required for dNTP synthesis. 30 This reversibly blocks the replication fork in S-phase and may also cause DNA fragmentation and chromosomal abnormalities. 30,31 If the putative Arabidopsis CDC25 gene has the conserved Cdc25 function, we expected that overexpressing plants should show hypersensitivity towards genotoxic stress similar to the situation in human cells.…”
Section: Assessing the Function Of The Putative Arabidopsis Cdc25 Undmentioning
confidence: 99%
“…30 This reversibly blocks the replication fork in S-phase and may also cause DNA fragmentation and chromosomal abnormalities. 30,31 If the putative Arabidopsis CDC25 gene has the conserved Cdc25 function, we expected that overexpressing plants should show hypersensitivity towards genotoxic stress similar to the situation in human cells. 12,32 However, neither the gainnor the loss-of-function mutants showed a phenotype distinguishable from the wild type (Fig.…”
Section: Assessing the Function Of The Putative Arabidopsis Cdc25 Undmentioning
confidence: 99%